Tissue-specific expression of Ruby in Mexican lime (C. aurantifolia) confers anthocyanin accumulation in fruit - Thilmony, Roger; Dasgupta, Kasturi; Shao, Min; Harris, Daren; Hartman, Jake; Harden, Leslie A.; Chan, Ron; Thomson, James G. (Frontiers in Plant Science, 2022)
Tissue specific promoters are important tools for the precise genetic engineering of crop plants. Four fruit-preferential promoters were examined for their ability to confer a novel fruit trait in transgenic Mexican lime (C. aurantifolia). The Ruby transcription factor activates fruit anthocyanin accumulation within Moro blood orange and has been shown to function in activating anthocyanin accumulation in heterologous plant species. Although the CitVO1, CitUNK, SlE8 and PamMybA promoters were previously shown to confer strong fruit-preferential expression in transgenic tomato, they exhibited no detectable expression in transgenic Mexican lime trees. In contrast, the CitWax promoter exhibited high fruit-preferential expression of Ruby, conferring strong anthocyanin accumulation within the fruit juice sac tissue and moderate activity in floral/reproductive tissues. In some of the transgenic trees with high levels of flower and fruit anthocyanin accumulation, juvenile leaves also exhibited purple coloration, but the color disappeared as the leaves matured. We show that the CitWax promoter enables the expression of Ruby to produce anthocyanin colored fruit desired by consumers. The production of this antioxidant metabolite increases the fruits nutritional value and may provide added health benefits.